Dental Identifications of Adolf Hitler and Eva Braun - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2014)
Hitler [1] had very bad teeth and a very bad breath. Before the war, he asked Blaschke, his dentist, to immobilize his teeth with a dental bridge. He wanted that bridge to be placed for several years. Thus, Blaschke made an unusual and easy-to-recognize solid metal bridge.